2006
DOI: 10.1161/circulationaha.105.000786
|View full text |Cite
|
Sign up to set email alerts
|

Glucose-Insulin-Potassium and Tri-Iodothyronine Individually Improve Hemodynamic Performance and Are Associated With Reduced Troponin I Release After On-Pump Coronary Artery Bypass Grafting

Abstract: Background— Both glucose-insulin-potassium (GIK) and tri-iodothyronine (T3) may improve cardiovascular performance after coronary artery surgery (CABG) but their effects have not been directly compared and the effects of combined treatment are unknown. Methods and Results— In 2 consecutive randomized double-blind placebo-controlled trials, in patients undergoing first time isolated on-pump CABG between January 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(55 citation statements)
references
References 26 publications
(29 reference statements)
2
49
0
4
Order By: Relevance
“…Furthermore, T 3 cardioprotection was shown to be mediated via the suppression of the pro-apoptotic p38MAPK signaling pathway and be TRa1 receptor dependent (13,25). More importantly, in accordance with this experimental evidence, T 3 treatment resulted in marked increase of post-surgery cardiac function in patients undergoing cardiac bypass operations (27,28). Table 5 Multivariate linear regression analysis revealed that T 3 at 6 mo and gender and high-density lipoprotein (HDL) at early phase were independent predictors of myocardial function recovery (DEF%) after acute myocardial infarction.…”
Section: Th and Early Functional Recoverysupporting
confidence: 59%
“…Furthermore, T 3 cardioprotection was shown to be mediated via the suppression of the pro-apoptotic p38MAPK signaling pathway and be TRa1 receptor dependent (13,25). More importantly, in accordance with this experimental evidence, T 3 treatment resulted in marked increase of post-surgery cardiac function in patients undergoing cardiac bypass operations (27,28). Table 5 Multivariate linear regression analysis revealed that T 3 at 6 mo and gender and high-density lipoprotein (HDL) at early phase were independent predictors of myocardial function recovery (DEF%) after acute myocardial infarction.…”
Section: Th and Early Functional Recoverysupporting
confidence: 59%
“…This condition is described as nonthyroidal illness syndrome (NTIS), euthyroid sick syndrome or TACITUS (thyroid allostasis in critical illness, tumors, uremia and starvation) and is accompanied by increased mortality and morbidity [3,4]. Several trials have demonstrated improved surrogate parameters after substitution therapy with T 3 in NTIS [5,6]. It could not be proven, however, that therapy with T 4 or T 3 ameliorates the overall outcome of affected patients [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, T3 may be considered as suitable therapeutic option for hemodynamic support in the setting of ischemia-reperfusion. This concept is now supported by recent data from Ranasinghe et al showing that T3 treatment during by-pass surgery increased cardiac index while limited the troponin release [63].…”
Section: Th At Reperfusion: Function Versus Apoptosismentioning
confidence: 64%